A cross-sectional survey of adrenal steroid hormones among overweight/obese boys according to puberty stage - Bingyan Cao; Chunxiu Gong; Di Wu; Xuejun Liang; Wenjing Li; Min Liu; Chang Su; Miao Qin; Xi Meng; Liya Wei (BMC, 2019)
Abstract Background Obesity is associated with many chronic diseases including cortisol rhythm disorder and low testosterone. Furthermore, studies on obese children are quite limited and no concordance results have been obtained, especially for boys in puberty. Moreover, the sample sizes of previous studies were small, and were not representative. Methods We conducted a cross-sectional survey including 1148 boys aged 6-14 years, they were divided into overweight/obesity (OW/OB) group and normal weight (NW) group. Puberty status was assessed according to Tanner scale and testicular volume. Serum levels of pregnenolone, 17-OH progesterone, corticosterone, dehydroepiandrosterone (DHEA), and androstenedione were detected by LC-MS. Serum free testosterone and sex hormone-binding globulin (SHBG) levels were measured by chemiluminescence immunoassay. Results The 17-OH progesterone, DHEA, androstenedione and free testosterone levels of OW/OB boys at prepubertal stage or at the age 6 = < 10 years group were higher than those of the NW boys (all the P values were < 0.01). Furthermore, androstenedione and free testosterone levels were lower in OW/OB boys at late puberty, and the trend continued at the post pubertal stage for FT (P < 0.01-0.05). DHEA, androstenedione, and FT levels persisted to be higher at the 10~ < 12 years in OW/OB boys but not for 17-OH progesterone. FT level was lower in the OW/OB group at the 12~ < 15 years group. The SHBG levels in the OW/OB boys were lower than those in the NW ones at the 6~12 years group, and prepubertal to early pubertal stage. Conclusions Premature adrenarche is more likely in OW/OB boys. More attention should be given to the lower androgen levels of OW/OB boys at late pubertal and post pubertal stages.